Electrokinetically-Driven Assembly of Gold Colloids into Nanostructures for Surface-Enhanced Raman Scattering - Hannah Dies; Adam Bottomley; Danielle Lilly Nicholls; Kevin Stamplecoskie; Carlos Escobedo; Aristides Docoslis (Nanomaterials, 2020)
Surface-enhanced Raman scattering (SERS) enables the highly sensitive detection of (bio)chemical analytes in fluid samples; however, its application requires nanostructured gold/silver substrates, which presents a significant technical challenge. Here, we develop and apply a novel method for producing gold nanostructures for SERS application via the alternating current (AC) electrokinetic assembly of gold nanoparticles into two intricate and frequency-dependent structures: (1) nanowires, and (2) branched “nanotrees”, that create extended sensing surfaces. We find that the growth of these nanostructures depends strongly on the parameters of the applied AC electric field (frequency and voltage) and ionic composition, specifically the electrical conductivity of the fluid. We demonstrate the sensing capabilities of these gold nanostructures via the chemical detection of rhodamine 6G, a Raman dye, and thiram, a toxic pesticide. Finally, we demonstrate how these SERS-active nanostructures can also be used as a concentration amplification device that can electrokinetically attract and specifically capture an analyte (here, streptavidin) onto the detection site.